A carbon dot corrosion inhibitor based on vinasse waste liquid and a preparation method and application thereof

CN123002827APending Publication Date: 2026-10-30JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611113237.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明所要解决的技术问题是:现有缓蚀剂多采用化学合成法制备,存在原料成本高、工艺复杂、环境毒性大等缺陷,且在高氧、高盐等极端苛刻环境下的缓蚀效果难以达到预期目标;同时,酒糟废液作为大宗生物质废弃物,有机物含量高、处理成本大,亟需高附加值利用途径

Benefits of technology

[0022](1)通过以酒糟废液为碳源,采用一步水热法制备碳点缓蚀剂,实现了工业废液的资源化利用。酒糟废液作为白酒生产过程中的大宗生物质废弃物,有机物含量高、处理成本大,将其转化为高附加值的缓蚀剂产品,不仅降低了碳点缓蚀剂的制备成本,而且避免了酒糟废液直接排放对土壤和水体造成的污染,制备过程无需额外添加化学试剂,不产生二次污染,符合绿色化学理念。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002827A_ABST
    Figure CN123002827A_ABST
Patent Text Reader

Abstract

The application discloses a kind of carbon dots corrosion inhibitor based on distiller's grains waste liquid and its preparation method and application, belong to nanometer material preparation and metal protection technical field.The method is with distiller's grains waste liquid as carbon source, after mixing with water, hydrothermal reaction is carried out, and carbon dot corrosion inhibitor is obtained by suction filtration, centrifugation, dialysis and freeze drying.The carbon dot particles prepared are spherical or spherical, the average particle size is 1 to 100 nanometers, the surface is rich in hydroxyl, carboxyl and amine functional groups, with graphite carbon lattice stripe.It is prepared into 50 to 200 mg / L aqueous solution, and is added to oxygen-containing and / or salt-containing corrosive medium, and P110 steel or N80 steel is protected by corrosion at 50 to 200 DEG C.The application realizes the resource utilization of distiller's grains waste liquid, and the preparation process is simple and green, and the carbon dot corrosion inhibitor has significant corrosion inhibition effect in high salt, high oxygen and high salt and high oxygen environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterial preparation and metal protection technology, specifically relating to a carbon point corrosion inhibitor based on distillery waste liquid, its preparation method and application. Background Technology

[0002] As oil and gas extraction expands into deep wells, long-distance pipelines, and highly corrosive formations, corrosion problems in oil pipe steels such as P110 and N80 are becoming increasingly severe during service. Especially during water injection development and tertiary oil recovery, the tubing is exposed to complex corrosive media of high oxygen and high salinity for extended periods, making it highly susceptible to uniform corrosion or localized pitting corrosion. This not only shortens the service life of the pipes and increases production costs but can also lead to serious oil and gas leaks, posing significant threats to safe production and the ecological environment. Currently, adding corrosion inhibitors is the most common and economical method to suppress metal corrosion. However, traditional chemically synthesized corrosion inhibitors, such as imidazoline and phosphate inhibitors, often suffer from complex synthesis processes, high costs, and significant environmental toxicity. Furthermore, their corrosion inhibition effects and thermal stability under extreme conditions such as high oxygen and high salinity are often unsatisfactory. Carbon dots, as a novel zero-dimensional nanomaterial, possess abundant surface functional groups (such as hydroxyl, carboxyl, and amino groups), excellent solubility, and environmental friendliness, demonstrating enormous application potential in the field of metal protection. However, current raw materials for carbon dot preparation largely rely on high-purity chemical reagents, such as citric acid and ethylenediamine, resulting in high production costs and limiting their large-scale industrial application. Furthermore, the development of highly efficient and green carbon dot corrosion inhibitors for specific corrosive environments with high oxygen and high salinity is still in its early stages, lacking stable and widely available low-cost products. On the other hand, distiller's grains waste liquid, a major biomass waste generated during the production of baijiu (Chinese liquor), has extremely high organic content, including sugars, proteins, and organic acids. Direct discharge would cause severe soil and water pollution, with extremely high treatment costs. Since distiller's grains waste liquid is rich in elements such as carbon and nitrogen, its resource utilization and conversion into high-value-added carbon dot materials can not only effectively solve the waste liquid treatment problem and reduce the production cost of corrosion inhibitors, but also achieve the recycling of biomass resources.

[0003] Therefore, developing a highly efficient and green carbon point corrosion inhibitor prepared from distiller's grains waste liquid for P110 and N80 steels under high oxygen and high salt environments has significant engineering application value and remarkable social and environmental significance. Summary of the Invention

[0004] The technical problem to be solved by this invention is that existing corrosion inhibitors are mostly prepared by chemical synthesis, which has the disadvantages of high raw material cost, complex process and high environmental toxicity. Moreover, the corrosion inhibition effect is difficult to achieve the expected target under extreme harsh environments such as high oxygen and high salt. At the same time, as a large amount of biomass waste, distiller's grains waste liquid has a high organic content and high treatment cost, and urgently needs a high value-added utilization method.

[0005] To solve the above-mentioned technical problems, the present invention provides a method for preparing a carbon point corrosion inhibitor based on distiller's grains waste liquid, comprising the following steps:

[0006] Step S100: Take the waste liquid of distiller's grains, let it stand, and then mix it evenly with water. The volume fraction of the waste liquid of distiller's grains is 40 to 60 parts, the volume fraction of water is 40 to 60 parts, and the sum of the two is 100 parts.

[0007] Step S200: Transfer the mixture into a hydrothermal reactor and react at 170 to 190°C for 10 to 14 hours;

[0008] Step S300: Filter the hydrothermal reaction product to remove carbon residue and collect the filtrate;

[0009] Step S400: Centrifuge the filtrate at 10,000 rpm to remove residual micro-suspended matter and collect the supernatant;

[0010] Step S500: Transfer the supernatant into a dialysis bag with a molecular weight cutoff of 500 Daltons and perform water dialysis under light-protected conditions until the color of the dialysate shows no obvious change.

[0011] Step S600: Freeze-dry the dialyzed solution to obtain a brown or brownish-black powder, which is the carbon point corrosion inhibitor based on distillers' grains waste liquid.

[0012] Furthermore, in step S100, the volume fraction of the waste liquor is 50 parts and the volume fraction of the water is 50 parts; in step S200, the hydrothermal reaction temperature is 180℃ and the reaction time is 12 hours.

[0013] The present invention also provides a carbon point corrosion inhibitor based on distiller's grains waste liquid prepared by the above method.

[0014] Furthermore, the carbon dots are spherical or near-spherical with an average particle size of 1 to 100 nanometers, and the carbon dots have graphite carbon lattice striations with a crystal interplanar spacing of 0.21 to 0.34 nanometers.

[0015] Furthermore, the infrared spectrum of carbon dots at wavenumber 3400 cm⁻¹ -1 The characteristic absorption peak appearing at 1650 cm⁻¹ is attributed to the stretching vibration of the hydroxyl group. -1 The characteristic absorption peak appearing at 1400 cm⁻¹ is attributed to the stretching vibration of the carbonyl group. -1 The characteristic absorption peaks appearing at this point are attributed to the stretching vibrations of the carbon-nitrogen bond.

[0016] Furthermore, the mass percentages of carbon, nitrogen, and oxygen in the carbon dots are 60% to 75% carbon, 5% to 15% nitrogen, and 15% to 30% oxygen, respectively.

[0017] Furthermore, the mass percentages of carbon, nitrogen, and oxygen in the carbon dots are 68% to 72% carbon, 8% to 12% nitrogen, and 18% to 22% oxygen, respectively.

[0018] Furthermore, the UV-Vis absorption spectrum of carbon dots shows a characteristic absorption peak at 270 to 290 nm, which is attributed to the n-π* transition of the carbon-oxygen double bond; the fluorescence emission peak of carbon dots is located at 420 to 480 nm.

[0019] The present invention also provides the application of the above-mentioned distillery waste liquid-based carbon point corrosion inhibitor, wherein the distillery waste liquid-based carbon point corrosion inhibitor is prepared into an aqueous solution with a concentration of 50 to 200 mg / L, and added to an oxygen-containing and / or salt-containing corrosive medium at a temperature of 50 to 200°C for corrosion inhibition protection of P110 steel or N80 steel.

[0020] Furthermore, the mass concentration of sodium chloride in the salt-containing corrosive medium is 1% to 15%, and the mass concentration of hydrogen peroxide in the oxygen-containing corrosive medium is 1% to 10%.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] (1) By using distillery waste liquid as a carbon source and employing a one-step hydrothermal method to prepare carbon point corrosion inhibitors, the resource utilization of industrial waste liquid has been realized. Distillery waste liquid is a major biomass waste in the process of liquor production. It has a high organic content and high treatment cost. Converting it into a high-value-added corrosion inhibitor product not only reduces the preparation cost of carbon point corrosion inhibitors, but also avoids the pollution of soil and water caused by the direct discharge of distillery waste liquid. The preparation process does not require the addition of additional chemical reagents and does not generate secondary pollution, which is in line with the concept of green chemistry.

[0023] (2) The prepared carbon point corrosion inhibitor exhibits significant corrosion inhibition effects on N80 steel and P110 steel under various harsh environments, including high salt, high oxygen, and high salt and high oxygen environments. The corrosion inhibition efficiency can reach over 90% in high salt environments and 50% to 60% in high oxygen environments. It also shows significant corrosion inhibition in combined high salt and high oxygen environments. Electrochemical tests show that the addition of the carbon point corrosion inhibitor shifts the corrosion potential positively by 100 to 200 millivolts, expands the capacitive arc, and effectively inhibits the corrosion reaction on the steel surface.

[0024] (3) The preparation process is simple and the reaction conditions are mild, without the need for extreme conditions such as high temperature and high pressure. The hydrothermal reaction temperature is only 170 to 190℃ and the reaction time is 10 to 14 hours. The product can be obtained by filtration, centrifugation, dialysis and freeze drying. The operation steps are simple and easy to scale up for industrial production. The prepared carbon dot particles have an average particle size of 1 to 100 nanometers, uniform particle size distribution, good solubility and easy on-site addition.

[0025] The present invention will now be further described with reference to the accompanying drawings. Attached Figure Description

[0026] Figure 1 Tafel curves showing the corrosion inhibition effect of carbon dots on N80 steel under high oxygen and high salt conditions.

[0027] Figure 2 The Nyquist curve shows the corrosion inhibition effect of carbon dots on N80 steel under high oxygen and high salt conditions.

[0028] Figure 3 Tafel curves showing the corrosion inhibition effect of carbon dots on P110 steel under high oxygen conditions.

[0029] Figure 4 The Nyquist curve shows the corrosion inhibition effect of carbon dots on P110 steel under high oxygen conditions.

[0030] Figure 5 Tafel curves showing the corrosion inhibition effect of carbon dots on N80 steel under high oxygen conditions.

[0031] Figure 6 The Nyquist curve shows the corrosion inhibition effect of carbon dots on N80 steel under high oxygen conditions.

[0032] Figure 7 Tafel curves showing the corrosion inhibition effect of carbon dots on N80 steel under high-salt conditions.

[0033] Figure 8 The Nyquist curve shows the corrosion inhibition effect of carbon dots on N80 steel under high-salt conditions. Detailed Implementation

[0034] The specific embodiments of the present invention will be described in further detail below, but the scope of protection of the present invention is not limited thereto. Any improvements or substitutions based on the basic spirit of these embodiments still fall within the scope of protection claimed by the claims of the present invention. In the present invention, unless otherwise specified, the raw materials and equipment used are commercially available products. In the following embodiments, unless otherwise specified, they are conventional methods in the art. The various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0035] Preparation method; This invention provides a method for preparing a carbon point corrosion inhibitor based on distiller's grains waste liquid, comprising the following steps:

[0036] Step S100: Take the waste liquor from the distiller's grains, let it stand, and then mix it evenly with water. The volume fraction of the waste liquor from the distiller's grains is 40 to 60 parts, and the volume fraction of the water is 40 to 60 parts, with the sum of the two being 100 parts.

[0037] Step S200: Transfer the mixture into a hydrothermal reactor and react at 170~190℃ for 10~14 hours.

[0038] Step S300: Filter the hydrothermal reaction product to remove carbon residue and collect the filtrate.

[0039] Step S400: Centrifuge the filtrate at 10,000 rpm to remove residual small suspended matter and collect the supernatant.

[0040] Step S500: Transfer the supernatant into a dialysis bag with a molecular weight cutoff of 500 Daltons and perform water dialysis under light-protected conditions until the color of the dialysate shows no obvious change.

[0041] Step S600: Freeze-dry the dialyzed solution to obtain a brown or brownish-black powder, which is the carbon point corrosion inhibitor based on distillers' grains waste liquid.

[0042] Product Characterization: The carbon dot corrosion inhibitor based on distiller's grains prepared by the above method has spherical or near-spherical particles with an average particle size of 1-100 nm, uniform particle size distribution, interplanar spacing of 0.21-0.34 nm, and graphite carbon lattice fringes. The infrared spectrum of the carbon dots at wavenumber 3400 cm⁻¹... -1 The characteristic absorption peak appearing at 1650 cm⁻¹ is attributed to the stretching vibration of the hydroxyl group. -1 The characteristic absorption peak appearing at 1400 cm⁻¹ is attributed to the stretching vibration of the carbonyl group. -1 The characteristic absorption peaks appearing at the carbon-nitrogen bond are attributed to stretching vibrations, indicating that the carbon dot surface is rich in functional groups such as hydroxyl, carboxyl, and amine groups. The UV-Vis absorption spectrum of the carbon dots shows a characteristic absorption peak at 270–290 nm, attributed to the n-π* transition of the carbon-oxygen double bond. The fluorescence emission peak of the carbon dots is located at 420–480 nm, emitting blue fluorescence under UV irradiation. X-ray photoelectron spectroscopy of the carbon dots shows that the mass percentages of carbon, nitrogen, and oxygen are 60%–75% carbon, 5%–15% nitrogen, and 15%–30% oxygen, respectively. These surface functional groups enable the carbon dots to adhere to the metal surface through chemisorption and physisorption, forming a dense protective film that prevents corrosive media from contacting the metal substrate.

[0043] Application Method: The carbon point corrosion inhibitor based on distillers' grains waste liquid of the present invention is prepared into an aqueous solution with a concentration of 50-200 mg / L, and added to an oxygen-containing and / or salt-containing corrosive medium at a temperature of 50-200℃ for corrosion inhibition and protection of P110 steel or N80 steel. The mass concentration of sodium chloride in the salt-containing corrosive medium is 1%-15%, and the mass concentration of hydrogen peroxide in the oxygen-containing corrosive medium is 1%-10%. The carbon point corrosion inhibitor is uniformly dispersed in the corrosive medium. The carbon point particles coordinate with iron atoms on the steel surface through surface functional groups, adsorbing onto the steel surface to form a nanoscale protective layer, inhibiting the anodic dissolution process and cathodic oxygen reduction process of the corrosion reaction, thereby reducing the corrosion rate.

[0044] In Example 1, distiller's grains waste liquid was mixed with water at a volume ratio of 1:1, and the hydrothermal reaction temperature was 180°C for 12 hours. Subsequently, the mixture was filtered, centrifuged, dialyzed, and freeze-dried according to steps S300 to S600 to obtain carbon dot powder. The obtained carbon dot particles had an average particle size of 2-10 nanometers, emitted bright blue fluorescence under ultraviolet light, and characteristic absorption peaks of hydroxyl, carbonyl, and carbon-nitrogen bonds were detected by infrared spectroscopy.

[0045] Example 2: The carbon dots prepared in Example 1 were formulated into a corrosion inhibitor solution with a concentration of 100 mg / L. The test steel was N80 steel, and the test environment was a high-salt, high-oxygen environment at 170°C, containing 10 wt% sodium chloride and 5 wt% hydrogen peroxide. A corrosion experiment was conducted in a high-pressure reactor for 72 hours. By weight loss analysis, the average mass loss rate of the blank group was 2.342%, the average mass loss rate of the carbon dot group was 1.704%, and the corrosion inhibition efficiency was 27.2%. (Refer to...) Figure 1 and Figure 2 Electrochemical test results showed that the Tafel curve indicated a positive shift in corrosion potential of approximately 200 millivolts, and the Nyquist plot showed an expansion of the capacitive arc in the low-frequency region, indicating that carbon dots effectively inhibited the corrosion reaction on the steel surface.

[0046] Example 3: The carbon dots prepared in Example 1 were formulated into a corrosion inhibitor solution with a concentration of 100 mg / L. The test steel was P110 steel, and the test environment was a high-oxygen environment at 170°C containing 5 wt% hydrogen peroxide. The corrosion experiment was conducted for 72 hours. The average mass loss rate of the blank group was 1.794%, the average mass loss rate of the carbon dot group was 0.852%, and the corrosion inhibition efficiency was 52.5%. (Refer to...) Figure 3 and Figure 4 Electrochemical tests showed that the corrosion potential shifted positively by about 100 millivolts, and the capacitive arc in the low-to-medium frequency range expanded.

[0047] Example 4: The carbon dots prepared in Example 1 were formulated into a corrosion inhibitor solution with a concentration of 100 mg / L. The test steel was N80 steel, and the test environment was a high-oxygen environment at 170°C containing 5 wt% hydrogen peroxide. The corrosion experiment was conducted for 72 hours. The average mass loss rate of the blank group was 1.893%, the average mass loss rate of the carbon dot group was 0.727%, and the corrosion inhibition efficiency was 61.6%. (Refer to...) Figure 5 and Figure 6 Electrochemical tests showed a positive shift in corrosion potential and an expansion of the capacitive arc.

[0048] Example 5: The carbon dots prepared in Example 1 were formulated into a corrosion inhibitor solution with a concentration of 100 mg / L. The test steel was N80 steel, and the test environment was a high-salt environment at 170°C containing 10 wt% sodium chloride. A corrosion experiment was conducted for 72 hours. The average mass loss rate of the blank group was 1.172%, the average mass loss rate of the carbon dot group was 0.113%, and the corrosion inhibition efficiency was 90.4%. (Refer to...)Figure 7 and Figure 8 Electrochemical tests showed that the corrosion potential shifted positively by about 100 millivolts, and the capacitive arc in the low-to-medium frequency range expanded.

[0049] As can be seen from the above embodiments, the carbon point corrosion inhibitor based on distiller's grains waste liquid prepared by the present invention has a significant corrosion inhibition effect on N80 steel and P110 steel under various harsh environments such as high salt, high oxygen and high salt and high oxygen, especially in high salt environment the corrosion inhibition efficiency can reach more than 90%.

Claims

1. A method for preparing a carbon point corrosion inhibitor based on distiller's grains waste liquid, characterized in that, Includes the following steps: Step S100: Take the waste liquid of distiller's grains, let it stand, and then mix it evenly with water. The volume fraction of the waste liquid of distiller's grains is 40 to 60 parts, the volume fraction of water is 40 to 60 parts, and the sum of the two is 100 parts. Step S200: Transfer the mixture into a hydrothermal reactor and react at 170 to 190°C for 10 to 14 hours; Step S300: Filter the hydrothermal reaction product to remove carbon residue and collect the filtrate; Step S400: Centrifuge the filtrate at 10,000 rpm to remove residual micro-suspended matter and collect the supernatant; Step S500: Transfer the supernatant into a dialysis bag with a molecular weight cutoff of 500 Daltons and perform water dialysis under light-protected conditions until the color of the dialysate shows no obvious change. Step S600: Freeze-dry the dialyzed solution to obtain a brown or brownish-black powder, which is the carbon point corrosion inhibitor based on distillers' grains waste liquid.

2. The preparation method according to claim 1, characterized in that, In step S100, the volume fraction of the waste liquid from distiller's grains is 50 parts, and the volume fraction of the water is 50 parts. In step S200, the hydrothermal reaction temperature is 180℃ and the reaction time is 12 hours.

3. A carbon point corrosion inhibitor based on distiller's grains waste liquid, characterized in that, It is prepared by the preparation method described in claim 1 or 2.

4. The distillers' grains waste liquid-based carbon point corrosion inhibitor according to claim 3, characterized in that, The carbon dots are spherical or near-spherical with an average particle size of 1 to 100 nanometers. The carbon dots have graphite carbon lattice striations with a crystal interplanar spacing of 0.21 to 0.34 nanometers.

5. The distillers' grains waste liquid-based carbon point corrosion inhibitor according to claim 3, characterized in that, The infrared spectrum of carbon dots at wavenumber 3400 cm⁻¹ -1 The characteristic absorption peaks appearing at this point are attributed to the stretching vibrations of the hydroxyl group; At wavenumber 1650 cm -1 The characteristic absorption peaks appearing at this point are attributed to the stretching vibrations of the carbonyl group; At wavenumber 1400 cm⁻¹ -1 The characteristic absorption peaks appearing at this point are attributed to the stretching vibrations of the carbon-nitrogen bond.

6. The distillers' grains waste liquid-based carbon point corrosion inhibitor according to claim 3, characterized in that, The mass percentages of carbon, nitrogen, and oxygen in carbon dots are 60% to 75%, 5% to 15%, and 15% to 30%, respectively.

7. The distillers' grains waste liquid-based carbon point corrosion inhibitor according to claim 6, characterized in that, The mass percentages of carbon, nitrogen, and oxygen in carbon dots are 68% to 72%, 8% to 12%, and 18% to 22%, respectively.

8. The distillers' grains waste liquid-based carbon point corrosion inhibitor according to claim 3, characterized in that, The UV-Vis absorption spectrum of carbon dots shows a characteristic absorption peak at 270 to 290 nm, which is attributed to the n-π* transition of the carbon-oxygen double bond; the fluorescence emission peak of carbon dots is located at 420 to 480 nm.

9. The application of a carbon point corrosion inhibitor based on distiller's grains waste liquid according to any one of claims 3 to 8, characterized in that, The carbon point corrosion inhibitor based on distillers' grains waste liquid is prepared into an aqueous solution with a concentration of 50 to 200 mg / L and added to an oxygen-containing and / or salt-containing corrosive medium at a temperature of 50 to 200°C for corrosion protection of P110 steel or N80 steel.

10. The application according to claim 9, characterized in that, The mass concentration of sodium chloride in salt-containing corrosive media is 1% to 15%, and the mass concentration of hydrogen peroxide in oxygen-containing corrosive media is 1% to 10%.